Negative ion flannel fabric and preparation method thereof
By applying negative ion coating on flannel fabric, combined with modified tourmaline powder and antibacterial composite components, the problem of insufficient washing resistance and negative ion release of existing negative ion textiles is solved, and the water washing resistance and antibacteriality of the fabric is improved Performance, improving indoor environment and human health.
Patent Information
- Application Number
- CN202411500748.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-20
AI Technical Summary
The existing negative ion textiles have shortcomings in washing resistance and negative ion release, and have fewer applications for flannel fabrics, which cannot effectively improve indoor microenvironment and human health.
By applying negative ion coating to the flannel fabric, the modified tourmaline, hydrophobic silicone emulsion and antibacterial composite components are used to form a negative ion coating to enhance the negative ion function, hydrophobic performance and antibacterial properties of the fabric.
It significantly improves the washing resistance, negative ion release and antibacterial properties of flannel fabrics, ensuring its stability and health during use.
Smart Images

Figure BDA0005102532970000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of fabrics, and in particular to a negative ion flannel fabric and a preparation method thereof. Background Art
[0002] Flannel is a soft and velvety wool fabric made from carded wool yarn. In China, it generally refers to a spun wool fabric with a clip-pattern style made from mixed-color carded wool yarn, which is covered with a layer of rich, fine and clean fluff, without revealing the texture, and feels soft and smooth.
[0003] With the improvement of living standards, people have higher and higher requirements for the comfort and health of indoor environment. Negative ions have multiple functions such as purifying air and promoting human metabolism. Therefore, applying negative ion technology to textiles has positive significance for improving indoor microenvironment and human health. However, existing negative ion textiles are mostly concentrated on products such as bedding and towels, and the application of flannel fabrics is relatively small. In addition, the existing negative ion textiles still need to be improved in terms of washability and negative ion release. Summary of the invention
[0004] In order to improve the above problems, the present application provides a negative ion flannel fabric and a preparation method thereof.
[0005] The negative ion flannel fabric and preparation method thereof provided in the present application adopt the following technical scheme: In the first aspect, the present application provides a negative ion flannel fabric, which adopts the following technical solution: A negative ion flannel fabric comprises a flannel fabric body and a negative ion coating, wherein the negative ion coating is obtained by coating a negative ion coating on the flannel fabric body, and the negative ion coating comprises a hydrophobic silicone emulsion, modified tourmaline powder, waterborne polyurethane, an antibacterial composite component, and a dispersant.
[0006] By adopting the above technical scheme, after the negative ion coating is applied on the surface of the flannel fabric, a negative ion coating is formed on the surface of the flannel fabric. After the modified tourmaline powder in the negative ion coating is combined with the flannel fabric, the flannel fabric has a negative ion function. The modified tourmaline powder can be better combined with the flannel fabric. At the same time, a hydrophobic silicone emulsion is added to the negative ion coating, which can make the flannel fabric have good hydrophobicity and breathability, and improve the washability of the flannel fabric. At the same time, the antibacterial composite component is added to further improve the antibacterial performance of the flannel fabric.
[0007] Preferably, the hydrophobic silicone emulsion is prepared by the following method: After mixing water, dodecylbenzenesulfonic acid and sodium dodecylsulfonate, stirring under oil bath conditions, adding octamethylcyclotetrasiloxane, vinyltriethoxysilane and methyltriethoxysilane, stirring to obtain an organosilicon preform; after mixing water, octadecyl methacrylate, hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, azobisisobutyronitrile and a surfactant, homogenizing to obtain a pre-emulsion, mixing the pre-emulsion with the organosilicon preform, stirring and reacting to obtain a hydrophobic organosilicon emulsion.
[0008] By adopting the above technical scheme, vinyl is introduced into silicone macromolecules to prepare a complex containing double bonds, which is copolymerized with long-chain monomers to prepare a hydrophobic silicone emulsion with good dispersibility and high stability. It can be well combined with flannel fabric, so that the surface tension of the treated flannel fabric is reduced, thereby improving the hydrophobic properties of the flannel fabric.
[0009] Preferably, the mass ratio between the organosilicon preform and the preformed emulsion is 1:(7.1-7.5).
[0010] By adopting the above technical solution, preferably the mass ratio between the organosilicon preform and the preformed emulsion is within the above range, the stability of the prepared hydrophobic organosilicon emulsion can be effectively improved.
[0011] Preferably, the surfactant comprises allyloxy nonylphenol polyoxyethylene ether ammonium sulfate.
[0012] Preferably, the antibacterial composite component comprises zein, carboxymethyl chitosan and curcumin.
[0013] By adopting the above technical scheme, curcumin is a natural polyphenol compound with a diketone structure, which has good antibacterial and antioxidant properties, carboxymethyl chitosan is a natural polymer material with excellent performance, and zein is a protein with hydrophobic properties. Curcumin, zein and carboxymethyl chitosan can form a complex with good antibacterial properties after being combined. After being combined with flannel fabric, the overall antibacterial properties of flannel fabric are improved, and at the same time, they can be compounded with hydrophobic silicone emulsion to improve the hydrophobic properties of flannel fabric.
[0014] Preferably, the antibacterial composite component is prepared by the following method: Zein and curcumin were added to an ethanol solution, carboxymethyl chitosan was added after stirring, ethanol was removed by rotary evaporation after stirring, and the solution was freeze-dried to obtain an antibacterial composite component.
[0015] By adopting the above technical scheme, zein and carboxymethyl chitosan are used as wall materials and curcumin is used as core material to prepare an antibacterial composite component, which has good dispersibility and long-term antibacterial performance, and can improve the antibacterial performance of flannel fabric. At the same time, zein and carboxymethyl chitosan have hydrogen bonding, electrostatic and hydrophobic interactions, and can be combined with hydrophobic silicone emulsion to synergistically improve the hydrophobic properties of flannel fabric, and can make the flannel fabric have good stability.
[0016] Preferably, the mass ratio of zein, carboxymethyl chitosan and curcumin is 1:1:(0.22-0.26).
[0017] By adopting the above technical solution, preferably the mass ratio of zein, carboxymethyl chitosan and curcumin is within the above range, which can effectively improve the stability of the prepared antibacterial composite component.
[0018] Preferably, the modified tourmaline powder is prepared by the following method: The tourmaline powder is mixed with water and then ultrasonicated. In an oil bath, carboxyl nanocellulose is added while stirring. After the reaction, vacuum filtration is performed and the nanocellulose composite tourmaline powder is obtained. The nanocellulose composite tourmaline powder is mixed with ethanol, wet-milled and then dried to obtain modified tourmaline powder.
[0019] By adopting the above technical scheme, the tourmaline powder is modified by carboxyl nanocellulose, and the fibrous carboxyl nanocellulose can produce a certain steric hindrance between the tourmalines, so that the tourmaline powder can be more evenly dispersed in the system, and can enhance the bonding effect between the tourmaline powder and the flannel fabric, thereby enhancing the long-term effect of the negative ion function of the flannel fabric.
[0020] Preferably, the mass ratio of the carboxyl nanocellulose to the tourmaline powder is 1:(5.8-6.4).
[0021] By adopting the above technical solution, preferably the mass ratio between carboxyl nanocellulose and tourmaline powder is within the above range, which can effectively improve the stability of the prepared modified tourmaline powder.
[0022] In a second aspect, the present application provides a method for preparing a negative ion flannel fabric, using the following technical solution: A method for preparing a negative ion flannel fabric comprises the following steps: The flannel fabric is completely immersed in the negative ion coating, and after standing, the flannel fabric is taken out and dried, so that a negative ion coating is formed on the surface of the flannel fabric to obtain the negative ion flannel fabric.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. After the negative ion coating is applied on the surface of the flannel fabric body, a negative ion coating is formed on the surface of the flannel fabric body, and the modified tourmaline in the negative ion coating is combined with the flannel fabric, so that the flannel fabric has a negative ion function. At the same time, after the hydrophobic silicone emulsion and the antibacterial composite component are added to the negative ion coating, the antibacterial performance and hydrophobic performance of the flannel fabric are improved; 2. The antibacterial composite component prepared by using zein and carboxymethyl chitosan as wall materials and curcumin as profile can effectively improve the antibacterial performance of flannel fabrics. At the same time, the curcumin is slowly released, thereby improving the long-term antibacterial performance of the antibacterial composite component. At the same time, zein has good hydrophobic properties and can synergistically improve the hydrophobic properties of flannel fabrics with hydrophobic silicone emulsions. 3. Nanocellulose creates steric hindrance between tourmalines, allowing tourmaline powder to be more evenly dispersed in the system and more stably combined with flannel fabric, thereby enhancing the negative ion function of flannel fabric. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments: Description of raw materials: All raw materials in the examples are commercially available; the surfactant in the hydrophobic silicone emulsion is 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate (CAS No.: 184719-88-8); the dispersant is BYK-194N; and the flannel fabric is polyester-cotton flannel.
[0025] Example 1 Preparation of hydrophobic silicone emulsion: 281 g of deionized water, 8.65 g of dodecylbenzenesulfonic acid (CAS No.: 27176-87-0) and 2.35 g of sodium dodecylsulfonate (CAS No.: 2386-53-0) were mixed, and the mixture was heated to 75 ° C in an oil bath, stirred at a speed of 350 r / min for 30 min, and then 78.75 g of octamethylcyclotetrasiloxane (CAS No.: 556-67-2), 7.5 g of vinyltriethoxysilane (CAS No.: 78-08-0) and 7.5 g of methyltriethoxysilane (CAS No.: 2031-67-6) were added, the temperature was maintained and stirred for 5 h, and the mixture was cooled to 25 ° C to obtain an organosilicon preform; 199.82 g of deionized water, 5.52 g of 2-methyl-2 -Octadecyle acrylate (CAS No.: 32360-05-7), 0.92g of hydroxyethyl acrylate (CAS No.: 818-61-1), 18.4g of butyl acrylate (CAS No.: 141-32-2), 18.4g of methyl methacrylate (CAS No.: 80-62-6), 0.74g of azobisisobutyronitrile (CAS No.: 78-67-1) and 1.84g of a surfactant were mixed, ultrasonically crushed and homogenized in a homogenizer for 30min to obtain a pre-emulsion, 78.61g of the pre-emulsion was heated to 70°C, and then 11.39g of the silicone preform was added and stirred at a speed of 300r / min. After adding, the mixture was kept warm for 3h and finally cooled to 25°C to obtain a hydrophobic silicone emulsion.
[0026] Preparation of antibacterial composite components: 18.02 g of zein (CAS No.: 9010-66-6) and 3.96 g of curcumin (CAS No.: 458-37-7) were added to 500 g of ethanol solution (the volume ratio of ethanol to deionized water was 4:1), and magnetic stirring was performed at 400 rpm for 2 h. Subsequently, 18.02 g of carboxymethyl chitosan (CAS No.: 83512-85-0) was added and stirred at 600 rpm for 2 h. The pH value of the system was adjusted to 6.5 with hydrochloric acid and sodium hydroxide, and the ethanol was removed by rotary evaporation. The mixture was freeze-dried at -20°C for 12 h to obtain an antibacterial composite component.
[0027] Preparation of modified tourmaline powder: 42.42 g of tourmaline powder was mixed with 200 g of deionized water and ultrasonicated for 10 min. The temperature was raised to 60°C in an oil bath, and 3.96 g of carboxyl nanocellulose was added while maintaining a rotation speed of 300 r / min. The temperature was maintained for 2 h. After vacuum filtration, the mixture was dried in a drying oven at 80°C for 2 h to obtain nanocellulose composite tourmaline powder. The nanocellulose composite tourmaline powder was mixed with ethanol, wet-milled for 10 h, and dried to obtain modified tourmaline powder.
[0028] Preparation of negative ion coating: 300 g of aqueous polyurethane was mixed with 40 g of hydrophobic silicone emulsion, stirred at 400 r / min for 2 h, then 20 g of modified tourmaline powder, 13 g of antibacterial composite component and 5 g of dispersant were added, and stirred at 600 r / min for 2 h to obtain a negative ion coating.
[0029] Preparation of negative ion flannel fabric: The flannel fabric is completely immersed in the negative ion coating, and after standing for 30 minutes, the flannel fabric is taken out and dried at 45° C. so that a negative ion coating is formed on the surface of the flannel fabric to obtain a negative ion flannel fabric.
[0030] Example 2 Preparation of hydrophobic silicone emulsion: 281 g of deionized water, 8.65 g of dodecylbenzenesulfonic acid and 2.35 g of sodium dodecylsulfonate were mixed, and the mixture was heated to 75°C in an oil bath, and stirred at a speed of 350 r / min for 30 min. Subsequently, 78.75 g of octamethylcyclotetrasiloxane, 7.5 g of vinyltriethoxysilane and 7.5 g of methyltriethoxysilane were added, and the temperature was maintained and stirred for 5 h, and the mixture was cooled to 25°C to obtain an organosilicon preform. 199.82 g of deionized water, 5.52 g of 2-methyl-2-propanediol and 1.2 g of ethyl acetate were added. Octadecyl acrylate, 0.92 g of hydroxyethyl acrylate, 18.4 g of butyl acrylate, 18.4 g of methyl methacrylate, 0.74 g of azobisisobutyronitrile and 1.84 g of a surfactant were mixed, ultrasonically crushed and homogenized in a homogenizer for 30 min to obtain a pre-emulsion, 79.41 g of the pre-emulsion was heated to 70°C, and then 10.59 g of the silicone preform was added and stirred at a speed of 300 r / min. After adding, the mixture was kept warm for 3 h and finally cooled to 25°C to obtain a hydrophobic silicone emulsion.
[0031] Preparation of antibacterial composite components: 17.7 g of zein and 4.6 g of curcumin were added to 500 g of ethanol solution (the volume ratio of ethanol to deionized water was 4:1), and magnetic stirring was performed at 400 rpm for 2 h. Subsequently, 17.7 g of carboxymethyl chitosan was added, and stirred at 600 rpm for 2 h. The pH value of the system was adjusted to 6.5 with hydrochloric acid and sodium hydroxide, and the ethanol was removed by rotary evaporation. The mixture was freeze-dried at -20°C for 12 h to obtain an antibacterial composite component.
[0032] Preparation of modified tourmaline powder: 43.06 g of tourmaline powder was mixed with 200 g of deionized water and ultrasonicated for 10 minutes. The temperature was raised to 60°C in an oil bath, and 6.94 g of carboxyl nanocellulose was added while maintaining a rotation speed of 300 r / min. The temperature was maintained for 2 hours. After vacuum filtration, the mixture was dried in a drying oven at 80°C for 2 hours to obtain nanocellulose composite tourmaline powder. The nanocellulose composite tourmaline powder was mixed with ethanol, wet-milled for 10 hours, and dried to obtain modified tourmaline powder.
[0033] Preparation of negative ion coating: 340 g of aqueous polyurethane was mixed with 50 g of hydrophobic silicone emulsion, stirred at 400 r / min for 2 h, then 26 g of modified tourmaline powder, 15 g of antibacterial composite component and 7 g of dispersant were added, and stirred at 600 r / min for 2 h to obtain a negative ion coating.
[0034] Preparation of negative ion flannel fabric: The flannel fabric is completely immersed in the negative ion coating, and after standing for 30 minutes, the flannel fabric is taken out and dried at 45° C. so that a negative ion coating is formed on the surface of the flannel fabric to obtain a negative ion flannel fabric.
[0035] Example 3 Preparation of hydrophobic silicone emulsion: 281 g of deionized water, 8.65 g of dodecylbenzenesulfonic acid and 2.35 g of sodium dodecylsulfonate were mixed, and the mixture was heated to 75°C in an oil bath, and stirred at a speed of 350 r / min for 30 min. Subsequently, 78.75 g of octamethylcyclotetrasiloxane, 7.5 g of vinyltriethoxysilane and 7.5 g of methyltriethoxysilane were added, and the temperature was maintained and stirred for 5 h, and the mixture was cooled to 25°C to obtain an organosilicon preform. 199.82 g of deionized water, 5.52 g of 2-methyl-2-propanediol and 1.2 g of ethyl acetate were added. Octadecyl acrylate, 0.92 g of hydroxyethyl acrylate, 18.4 g of butyl acrylate, 18.4 g of methyl methacrylate, 0.74 g of azobisisobutyronitrile and 1.84 g of a surfactant were mixed, ultrasonically crushed and homogenized in a homogenizer for 30 min to obtain a pre-emulsion, 79.02 g of the pre-emulsion was heated to 70°C, and then 10.98 g of the organosilicon preform was added and stirred at a speed of 300 r / min. After adding, the mixture was kept warm for 3 h and finally cooled to 25°C to obtain a hydrophobic organosilicon emulsion.
[0036] Preparation of antibacterial composite components: 17.86 g of zein and 4.28 g of curcumin were added to 500 g of ethanol solution (the volume ratio of ethanol to deionized water was 4:1), and magnetic stirring was carried out at 400 rpm for 2 h. Subsequently, 17.86 g of carboxymethyl chitosan was added, and stirred at 600 rpm for 2 h. The pH value of the system was adjusted to 6.5 with hydrochloric acid and sodium hydroxide, and the ethanol was removed by rotary evaporation. The mixture was freeze-dried at -20°C for 12 h to obtain an antibacterial composite component.
[0037] Preparation of modified tourmaline powder: 42.75 g of tourmaline powder was mixed with 200 g of deionized water and ultrasonicated for 10 minutes. The temperature was raised to 60°C in an oil bath, and 7.25 g of carboxyl nanocellulose was added at a speed of 300 r / min. The temperature was kept for reaction for 2 hours. After vacuum filtration, the mixture was dried in a drying oven at 80°C for 2 hours to obtain nanocellulose composite tourmaline powder. The nanocellulose composite tourmaline powder was mixed with ethanol, wet-milled for 10 hours, and dried to obtain modified tourmaline powder.
[0038] Preparation of negative ion coating: 320 g of aqueous polyurethane was mixed with 45 g of hydrophobic silicone emulsion, stirred at 400 r / min for 2 h, then 23 g of modified tourmaline powder, 14 g of antibacterial composite component and 6 g of dispersant were added, and stirred at 600 r / min for 2 h to obtain a negative ion coating.
[0039] Preparation of negative ion flannel fabric: The flannel fabric is completely immersed in the negative ion coating, and after standing for 30 minutes, the flannel fabric is taken out and dried at 45° C. so that a negative ion coating is formed on the surface of the flannel fabric to obtain a negative ion flannel fabric.
[0040] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the hydrophobic silicone emulsion, the amount of silicone preform added is 13.04 g, and the amount of preformed emulsion added is 76.96 g.
[0041] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the hydrophobic silicone emulsion, the amount of silicone preform added is 9.47 g, and the amount of preformed emulsion added is 80.53 g.
[0042] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the antibacterial composite component, 18.35 g of zein, 18.35 g of carboxymethyl chitosan and 3.3 g of curcumin are used.
[0043] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the antibacterial composite component, 17.39 g of zein, 17.39 g of carboxymethyl chitosan and 5.22 g of curcumin are used.
[0044] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, 41.67 g of tourmaline powder and 8.33 g of carboxyl nanocellulose are used in preparing modified tourmaline powder.
[0045] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing modified tourmaline powder, 43.75 g of tourmaline powder and 6.25 g of carboxyl nanocellulose are used.
[0046] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, when preparing the antibacterial composite component, only curcumin, carboxymethyl chitosan and zein are physically mixed.
[0047] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, when preparing the modified tourmaline powder, the nano-cellulose composite tourmaline powder is not wet ground.
[0048] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, no vinyltriethoxysilane is added when preparing the organosilicon preform.
[0049] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the modified tourmaline powder is replaced with ordinary tourmaline powder.
[0050] Comparative Example 3 Comparative Example 3 is based on Example 3, and in Comparative Example 3, the antibacterial composite component is replaced by curcumin.
[0051] Performance testing The samples of Examples 1-11 and Comparative Examples 1-3 were sampled and subjected to the following performance tests: (1) Negative ion function test Using GB / T 30128-2013 as the test standard, the negative ion release of the sample was tested. Each sample was tested 3 times, the average value was taken, and the test results were filled in Table 1.
[0052] (2) Washability test According to GB / T 5713-2013 as the test standard, the samples were washed and the negative ion release of the washed fabrics was retested. Each sample was tested 3 times, the average value was taken, and the test results were filled in Table 1.
[0053] (3) Hydrophobic performance test The contact angle of the sample surface was tested. Each sample was randomly tested three times, the average value was taken, and the test results were filled in Table 1.
[0054] (4) Antibacterial performance test Taking GB / T 18830-2009 Evaluation of UV protection of textiles as the testing standard, the prepared fabrics were tested for UV protection, and the antibacterial properties of the samples were tested after 7d and 90d respectively. Each sample was tested 3 times, and the average value was taken. The test results were filled in Table 1.
[0055] Table 1 Performance test results of samples of Examples 1-11 and Comparative Examples 1-3 Data analysis Combined with Table 1, it can be seen that the negative ion release of Examples 1-3 is all around 2900 / cm 3 The above indicates that the anion flannel fabric prepared by the present application has good anion release function. The anion release amount of Examples 1-3 after washing is 2500 / cm 3 And above, and the hydrophobic angles are all 135° and above, indicating that the negative ion flannel fabric prepared by the present application has good water washability; the antibacterial rates of Escherichia coli after 7 days in Examples 1-3 are all 99.50% and above, and the antibacterial rates of Staphylococcus aureus are all 99.50% and above, and the antibacterial rates of Escherichia coli after 90 days are all 96.00% and above, and the antibacterial rates of Staphylococcus aureus are all 96.00% and above, indicating that the negative ion flannel fabric prepared by the present application has a good antibacterial rate and can play a long-term antibacterial role.
[0056] In Example 4 and Example 5, when preparing the hydrophobic silicone emulsion, the mass ratio between the silicone preform and the preformed emulsion is not within the range specified in the present application. When the amount of the silicone preform added is too small, the conversion rate of the emulsion system is difficult to be further improved, and the uniformity of the emulsion particle size decreases, affecting the overall stability of the emulsion system; when the amount of the silicone preform added is too much, the low surface energy of the silicone preform affects the dispersion effect, the conversion rate of the emulsion decreases, and further affects the overall stability of the emulsion, and stratification occurs.
[0057] In Example 6 and Example 7, when preparing the antibacterial composite component, the mass ratios of zein, carboxymethyl chitosan and curcumin are not within the range specified in the present application. When the content of curcumin is too little, it is difficult to further increase the particle size of the prepared antibacterial composite component, thereby reducing the distribution uniformity of the antibacterial composite component in the negative ion coating; when the content of curcumin is too much, the average particle size of the system increases, and exceeds the loading capacity of the wall material for curcumin, so that part of the curcumin is attached to the surface of the composite, thereby increasing the particle size of the system, resulting in a decrease in the particle size uniformity, and affecting the stability of the antibacterial composite component.
[0058] In Example 8 and Example 9, when preparing modified tourmaline powder, the mass ratio of tourmaline powder to carboxyl nanocellulose is not within the scope of the present application. When the content of tourmaline powder is too little, the fibrous carboxyl nanocellulose is entangled with each other and it is difficult to interact with the tourmaline powder, resulting in a decrease in the dispersion uniformity of the tourmaline powder. When the content of tourmaline powder is too much, it is difficult for carboxyl nanocellulose to improve the surface of all the tourmaline powder, and some tourmaline powder agglomerates, affecting the overall stability of the system.
[0059] In Example 10, when preparing the antibacterial composite component, only curcumin, carboxymethyl chitosan and zein were physically mixed, and curcumin was difficult to be coated and quickly inactivated, making it difficult to exert long-term antibacterial performance. At the same time, the connection relationship between the antibacterial composite components decreased, and the stability decreased.
[0060] In Example 11, the nano-cellulose composite tourmaline component was not wet-milled, and the particle size uniformity of the unground tourmaline powder was difficult to improve, and it was difficult to evenly cover the surface of the flannel fabric, so the negative ion release of the flannel fabric decreased.
[0061] In Comparative Example 1, no vinyltriethoxysilane was added to the silicone preform, the proportion of long-chain silicone decreased, the overall stability and hydrophobicity of the emulsion system decreased, and the water resistance decreased.
[0062] In Comparative Example 2, ordinary unmodified tourmaline powder is added to the system. The surface energy of the unmodified tourmaline powder is difficult to be further improved. The tourmaline powder agglomerates in the system and is difficult to be evenly distributed on the surface of the flannel fabric, which affects the negative ion release of the flannel fabric.
[0063] In Comparative Example 3, the antibacterial component was replaced with curcumin. Uncoated curcumin was rapidly inactivated and it was difficult to exert long-term antibacterial performance. At the same time, the antibacterial performance was reduced after carboxymethyl chitosan was not added. Without zein, it was difficult to cooperate with the hydrophobic silicone emulsion to exert a hydrophobic effect.
[0064] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A negative ion flannel fabric, Features: The invention comprises a flannel fabric body and a negative ion coating, wherein the negative ion coating is obtained by coating the negative ion coating on the flannel fabric body, and the negative ion coating comprises a hydrophobic organic silicon emulsion, modified tourmaline powder, waterborne polyurethane, an antibacterial composite component and a dispersant.
2. The negative ion flannel fabric according to claim 1, Features: The hydrophobic silicone emulsion is prepared by the following method: After mixing water, dodecylbenzenesulfonic acid and sodium dodecylsulfonate, stirring under oil bath conditions, adding octamethylcyclotetrasiloxane, vinyltriethoxysilane and methyltriethoxysilane, stirring to obtain an organosilicon preform; after mixing water, octadecyl methacrylate, hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, azobisisobutyronitrile and a surfactant, homogenizing to obtain a pre-emulsion, mixing the pre-emulsion with the organosilicon preform, stirring and reacting to obtain a hydrophobic organosilicon emulsion.
3. The negative ion flannel fabric according to claim 2, Features: The mass ratio between the organosilicon preform and the preformed emulsion is 1:(7.1-7.5).
4. The negative ion flannel fabric according to claim 2, Features: The surfactant includes 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate.
5. The negative ion flannel fabric according to claim 1, Features: The antibacterial composite component comprises zein, carboxymethyl chitosan and curcumin.
6. The negative ion flannel fabric according to claim 5, Features: The antibacterial composite component is prepared by the following method: Zein and curcumin were added to an ethanol solution, carboxymethyl chitosan was added after stirring, ethanol was removed by rotary evaporation after stirring, and the solution was freeze-dried to obtain an antibacterial composite component.
7. The negative ion flannel fabric according to claim 5, Features: The mass ratio of zein, carboxymethyl chitosan and curcumin is 1:1:(0.22-0.26).
8. The negative ion flannel fabric according to claim 1, Features: The modified tourmaline powder is prepared by the following method: The tourmaline powder is mixed with water and then ultrasonicated. In an oil bath, carboxyl nanocellulose is added while stirring. After the reaction, vacuum filtration is performed and the nanocellulose composite tourmaline powder is obtained. The nanocellulose composite tourmaline powder is mixed with ethanol, wet-milled and then dried to obtain modified tourmaline powder.
9. The negative ion flannel fabric according to claim 8, Features: The mass ratio between the carboxyl nanocellulose and the tourmaline powder is 1:(5.8-6.4).
10. A method for preparing the negative ion flannel fabric according to claim 1, Features: The steps include: The flannel fabric is completely immersed in the negative ion coating, and after standing, the flannel fabric is taken out and dried, so that a negative ion coating is formed on the surface of the flannel fabric to obtain the negative ion flannel fabric.
